Validation and profile of Chinese pre-service teachers' technological pedagogical content knowledge scale. Issue 1 (1st January 2016) - Sang, Guoyuan; Tondeur, Jo; Chai, Ching Sing; Dong, Yan
Abstract : Researchers state that teachers in different contexts reported different technological pedagogical content knowledge (TPACK). This phenomenon may partially be explained by cultural differences. Based on this consideration, the development and validation of the Chinese pre-service teachers' technological pedagogical content knowledge (CTPCK) scale is described in this article. The sample was split into two subsamples on random basis ( n 1 = 229, n 2 = 207) for the purpose of conducting (1) exploratory factor analysis (EFA) and (2) confirmatory factor analysis (CFA), respectively. After the EFA, the CTPCK scale excluded six items and included eight factors with 42 items. Reliability and correlations were discussed. The findings revealed that the CTPCK scale was a valid and reliable instrument for measuring the TPACK of Chinese pre-service teachers' knowledge with or without linking educational technology.